The Differential Effects of Repetitive Magnetic Stimulation in an In Vitro Neuronal Model of Ischemia/Reperfusion Injury - Baek, Ahreum; Kim, Ji Hyun; Pyo, Soonil; Jung, Joon-Ho; Park, Eun Jee; Kim, Sung Hoon; Cho, Sung-Rae (Frontiers in Neurology, 2018)
Repetitive transcranial magnetic stimulation (rTMS) is a non-invasive therapy that has been implicated in treatment of serious neurological disorders. However, the neurobiological mechanisms underlying the effects of rTMS remain unclear. Therefore, this study examined the differential effects of repetitive magnetic stimulation (rMS) in an in vitro neuronal model of ischemia/reperfusion (I/R) injury, depending on low and high frequency. Neuro-2a (N2a) cells were differentiated with retinoic acid and established for in vitro neuronal model of I/R injury under a subsequent 3 hours of oxygen glucose deprivation/reoxygenation (OGD/R) condition. After the I/R injury, the differentiated neuronal cells were stimulated with rMS on day 1 and randomly divided into three groups: OGD/R+sham, OGD/R+low-frequency and OGD/R+high-frequency groups. High-frequency rMS increases cell proliferation through activation of extracellular signal-regulated kinases (ERK) and AKT signaling pathway and inhibits apoptosis in OGD/R injured cells. Furthermore, high-frequency rMS increases Ca2+- calmodulin-dependent protein kinase II (CaMKII)-cAMP-response element binding protein (CREB) signaling pathway, further leading to alternation of brain-derived neurotrophic factor (BDNF) expression and synaptic plasticity in OGD/R injured cells. These results verified the neurobiological mechanisms of frequency-dependent rMS in I/R injury-treated neuronal cells. These mechanisms will help develop more powerful and credible rTMS stimulation treatment protocols.